2016
DOI: 10.1139/cjpp-2015-0405
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of white horehound (Marrubium vulgare) extract against cyclophosphamide toxicity in male rats

Abstract: The hepatoprotective activity of Marrubium vulgare against cyclophosphamide toxicity in Wistar rats was evaluated. Adult male rats were divided into 4 groups of six each: a control group, a group injected with cyclophosphamide (150 mg/kg) for 3 days, a group orally given a Marrubium vulgare aqueous extract (500 mg of dry leaves /kg/day) for 30 days then treated with cyclophosphamide, and a group receiving only Marrubium vulgare for 30 days. After 33 days of treatment, activities of alanine amino transferase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…It has been determined that ROS plays an essential role in pathogenesis of DF-induced hepatic injuries and free radicals. Administration of olive leaves extract reduced the elevation of level plasma ASAT, ALAT, caused by DF due to preventing the decline of antioxidant defense system and direct free radical scavenging activity The protective effect of AEOL can be attributed to the presence of phenolic acids and flavonoids which are able to release a hydrogen proton from their hydroxyl-group trap free radicals and prevent DF induced liver damage (Ettaya et al 2016). Thus, HPLC analysis showed that AEOL is rich in phenolic acids (gallic acid, epicatechin, vanillic acid, coumaric acid and resveratrol) and flavonoids (rutin and apigenin).…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that ROS plays an essential role in pathogenesis of DF-induced hepatic injuries and free radicals. Administration of olive leaves extract reduced the elevation of level plasma ASAT, ALAT, caused by DF due to preventing the decline of antioxidant defense system and direct free radical scavenging activity The protective effect of AEOL can be attributed to the presence of phenolic acids and flavonoids which are able to release a hydrogen proton from their hydroxyl-group trap free radicals and prevent DF induced liver damage (Ettaya et al 2016). Thus, HPLC analysis showed that AEOL is rich in phenolic acids (gallic acid, epicatechin, vanillic acid, coumaric acid and resveratrol) and flavonoids (rutin and apigenin).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are a number of papers promising about phytochemical properties and biological activities of diverse Marrubium species (7,(11)(12)(13)(14)(15)(16)(17)(18)(19). However, there is no information about phytochemistry and biological potent of endemic species M. sivasense.…”
Section: Resultsmentioning
confidence: 99%
“…A previous phytochemical studies on Marrubium species resulted with polyphenols (7), essential oils (8), labdane diterpenoids and sterols (9,10). Biological activity investigations of Marrubium species encompasses antibacterial (11), antioxidant, antiproliferative (12), antinociceptive (13), antidiabetic (14), antihypertensive (15), hepatoprotective (16), antiinflammatory (17), cardioprotective (18) and cytotoxic/cytostatic (19) potentials. Some Marrubium species are traditionally used to treat various diseases, including asthma, pulmonary infections, inflammation and hypotension, as cholagogues and sedative agents, and for pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…Its aerial parts are official in Hungarian Pharmacopoeia VII [89], and the European Medicine Agency (EMA) approved in 2013 the treatment of cough associated to cold, mild dyspeptic complaints and temporary loss of appetite as indication for aerial part of this plant [90]. M. vulgare is reported to possess several biological activities, among which the most interesting are antihepatotoxic [91], antihyperglicemic [92], antibacterial [93], anti-inflammatory [94] and antioxidant properties [95]. In particular antioxidant properties may justify the widespread of Marrubium vulgare extracts, often prepared with peculiar extraction techniques, as natural cosmetic ingredients, with claims including anti-pollution, antioxidant, protective for irritated and stressed skin, detoxifying, soothing.…”
Section: Marrubium Vulgarementioning
confidence: 99%